2016
DOI: 10.5249/jivr.v8i1.630
|View full text |Cite
|
Sign up to set email alerts
|

Social determinants of child abuse: evidence of factors associated with maternal abuse from the Egypt demographic and health survey

Abstract: Abstract:Background:Child abuse or maltreatment is a significant global public health problem of unknown global prevalence. About 40 million children aged 0 - 14 years require health and social care globally. The prevalence, determinants, and trends of national or global rates of child abuse and maltreatment are largely unknown.Methods:Data for this retrospective cross-sectional study were derived from the 2005 Egyptian Demographic and Health Survey (2005 EDHS), and included 19474 women aged 15-49 years. Multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 29 publications
2
20
0
Order By: Relevance
“…Using a similar type of DHS instrument, previous studies also measured the attitudes toward wife beating in other countries like Armenia, Egypt, Ethiopia, India, Nepal, Nigeria, Pakistan, Palestine, etc. [e.g., 1 , 3 , 5 , 8 , 27 , 28 ]. These studies were mostly confined to the acceptance of wife beating.…”
Section: Introductionmentioning
confidence: 99%
“…Using a similar type of DHS instrument, previous studies also measured the attitudes toward wife beating in other countries like Armenia, Egypt, Ethiopia, India, Nepal, Nigeria, Pakistan, Palestine, etc. [e.g., 1 , 3 , 5 , 8 , 27 , 28 ]. These studies were mostly confined to the acceptance of wife beating.…”
Section: Introductionmentioning
confidence: 99%
“…[ 4 ] Children in the Arab Peninsula are exposed to all methods of CAN. [ 9 ] In spite of this, the literature has shown that CAN research remains scant with few scattered studies in Saudi Arabia,[ 10 11 12 13 ] Turkey,[ 3 ] Egypt,[ 14 ] and Jordan. [ 15 16 ] Other studies in the region have evaluated the perception of possible CAN among a variety of populations such as medical students,[ 17 ] pediatric physicians,[ 18 ] and preschool teachers (rather than parents).…”
Section: Introductionmentioning
confidence: 99%
“…The problem of CSA and the devastating short-and long-term health consequences, manifesting as physical, mental and psychiatric disorders, are well-documented. 1,6,7 The World Health Organization (WHO) has estimated that 40 million children annually are victims of child abuse and neglect by the age of 14 years 8,9. The psychological health problems that result from CSA are growing at an escalating rate 10,11.…”
mentioning
confidence: 99%